BETWEEN TRENDS AND JUDGEMENT: THE ROLE OF ONLINE FOMO AND FOPO IN SHAPING GENERATION Z’S IMPULSIVE BUYING BEHAVIOR - Nurrahmi Hayani; Darni Darni; Abdiana Ilosa; Saipul al sukri; Husaini Sulaiman (Jurnal Al-Iqtishad, 2026)
This study aims to explore the impact of Online Fear of Missing Out (On-FOMO) and Fear of Other People’s Opinions (FOPO) on online impulsive buying behavior among Generation Z in Pekanbaru. Using a quantitative descriptive design, data were collected from 342 valid respondents aged 14 to 29 through purposive sampling. The data were analyzed using multiple linear regression via SPSS 21.00. The results indicate that both On-FOMO and FOPO have a significant positive effect on impulsive buying, both partially and simultaneously. Specifically, On-FOMO triggers anxiety about missing trends, while FOPO drives the need for external validation and status symbols. The coefficient of determination shows that these variables contribute 20.6% to impulsive buying decisions. These findings imply that Gen Z’s consumption patterns have shifted from functional utility to symbolic identity validation. This research highlights how dual psychological pressures in the digital era override rational financial planning, turning impulsive shopping into a routine lifestyle. Consequently, there is an urgent need for enhanced digital financial literacy to mitigate these psychosocial vulnerabilities.